A is for Amish [large type] - Gray, Shelley Shepard (Gray, Shelley Shepard, Amish ABCs., 2025)
"Siblings Martin, Kelsey, Beth, and Jonny are as different as can be, but they have one thing in common. They're all longing to reinvent their lives. Raised by their divorced lapsed-Amish father and English mother, they only knew real stability and a sense of family when visiting their Old Order grandparents, Josiah and Sylvia Schrock, in peaceful Holmes County, Ohio. Now the four want to try living with them and joining their faith--much to the Schrocks' surprise... Martin, the eldest, is feeling dissatisfied with his life, and is determined to make a fresh start. When he meets his grandparents' neighbor, Patti Coblentz, he's immediately drawn to her outgoing, helpful nature--but is so overwhelmed that he appears blunt and rude. Is there any way he can drop his defenses enough to admit she's captured his heart? Always self-conscious about the birthmark on her temple, Patti is resigned to never marrying and busying herself with the responsibilities of the large home and property she has inherited. Yet given time and patience--and adhering to their grandparents' unexpectedly challenging rules--the whole family might just find what they're looking for, even Martin and Patti." --